Adichie’s Americanah: Remembering Home, Negotiating Identity - Cliff Feghabo, Charles (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
The remembrance of the homeland is fundamental to the negotiation of a transnational migrant’s cultural identity in the mélange of multiculturalism/transnationalism fostered by globalization. Available studies on Chimamanda Adichie’s Americanah dwell on race, gender and transcultural identity to the exclusion of memory and cultural identity relationship that is highlighted in the text. This essay draws from the Postcolonial theory – a theory that interrogates and reinterprets the cultural intercourse between the colonizing powers and the erstwhile colonies. Culture and power relationship is eloquent in Adichie’s text, consequently necessitating and validating the employment of the theory. This essay examines in the text the place of memory of the homeland in the negotiation of cultural identity in the diaspora. Americanah reveals some Nigerian diasporic characters in the United States of America and the United Kingdom. All but one of the diasporic characters suffer a mental disconnect from the homeland. Consequently, they easily sacrifice their cultural identity for a transnational identity. In contrast, the main character, Ifemelu, exhibits cultural fidelity through her mental interactions with the homeland and this catalyzes the negotiation of her cultural identity. Obvious through the actions of all the diasporic characters examined is that one’s cultural identity fidelity or otherwise is a function of one’s mental interface with or disconnection from the homeland.